A Model of the Effects of Self-efficacy on the Perceived Ethicality and Performance of Fear Appeals in Advertising - Snipes, Robin L. (Journal of business ethics, 1999)
The primary purpose of this study was to better understand the effects of consumers' perceived self-efficacy on their perceptions of the ethicality of a fear appeal and subsequent attitudes towards the ad, the brand, and purchase intentions. In this study, a total of 305 consumer responses were investigated to determine attitudes toward a fear appeal ad. The results suggest that the use of strong fear appeals may not be perceived as unethical if consumers feel they can use the recommended product to effectively eliminate the threat posed by the ad.